PENGUATAN ODHA TRANSPUAN KOTA DENPASAR DAN BULELENG DALAM KESEHATAN MASYARAKAT PEDULI WARIA - Zuryani, Nazrina (Jurnal Ilmiah Widya Sosiopolitika, 2021)
ABSTRACT This workshop on strengthening Transwomen with HIV/Aids (ODHAT) started from the issue of discrimination that often afflicts the LGBT and ODHATgroups. Transgender women or better known as waria are gender transfers from male to female. They are often embarrassed or humiliated to take part in society {especially for ODHA (People with HIV/Aids)}. In the city of Singaraja, Wargas have been formed as Transwomen organization that is actively developing their social and cultural capital in the community. Denpasar City has three units of official outreach institutions for LGBT, namely Gaya Dewata, Kerti Praja Foundation and Spirit Paramacita. The number of Transwomen with ODHA in Denpasar City is estimated at 40 people and in Singaraja City it is estimated at 11 people. They need to be protected from the stigma of society in other reachable and social media so that their communication patterns are more conducive and the community is more accepting of their existence. The 5-hour Tengkuluk Lelunakan make-up training was carried out by presenting the Warcan and Perwaron groups at Salon Agung on July 13, 2019. Ibu Agung as a salon owner who is famous for Payas Agung and Tengkuluk Lelunakan has facilitated them to learn tengkuluk lelunakan make-up. Denpasar city transgender groups are facilitated to perform in cultural events or other festivals, as has been done by Wargas in Singaraja city. However, correspondence with the Head of the Bali Provincial Culture Service in the office and with the initiator of the Sanur Village Festival at the Griya Santrian hotel has not produced results. The tengkuluk Lelunakan workshop for transwomen with ODHA aims to make the community accept them and finally be able to get access to various facilities to perform in public areas, especially in festivals in the city of Denpasar. Keywords:  transwomen, ODHAT, LGBT discrimination, Denpasar, Singaraja